Effectiveness of a parental school-based intervention to improve young children's eating patterns: a pilot study. Issue 13 (23rd April 2018) - Gomes, Ana Isabel; Barros, Luisa; Pereira, Ana Isabel; Roberto, Magda Sofia
Abstract: Objective: To evaluate the effectiveness of a pilot study of a parental school-based intervention to promote healthy eating behaviours in young children. Design: A quasi-experimental longitudinal design with three conditions (complete intervention (CIG), minimal intervention (MIG), control (CG)), with repeated measures at baseline, immediately after the intervention, 6 months and 1 year after intervention. Setting: Fourteen public and state-funded kindergartens near Lisbon, Portugal. Subjects: Parents ( n 349) of 3- to 6-year-old children assigned to the three conditions completed the baseline protocol. The 'Red Apple' intervention included four parental group sessions about young children's growth, nutritional guidelines and positive parental feeding strategies, which was combined with adult–child activities at home and in the classroom, and newsletters (CIG). MIG included only a single nutritional counselling session, whereas the CG had no intervention. At the end, thirty-eight, twenty-six and fifty-four parents in the CIG, MIG and CG, respectively, had completed all evaluation components. Data regarding parental perception of children's weight, self-efficacy, nutritional knowledge, feeding strategies, eating behaviours and BMI were collected at the four assessment moments. Results: The CIG showed improvements in children's healthy food intake, compared with the MIG and CG. Parental self-efficacy regarding the regulation of children's eating behaviours decreased in the CG but not in both intervention groups. Conclusions: Considering the low dosage of the intervention, the results obtained were positive. Future studies should offer additional solutions to overcome barriers to parents' participation.